THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES WITH THE PRACTICE OF CLEAN AND HEALTHY LIVING IN RANCAGOONG TANJUNGWANGI VILLAGE, TANJUNGMEDAR DISTRICT, SUMEDANG REGENCY IN 2022 - Marcelina , Sherly; Komala , Iis (PHSAJ - Public Health Sebelas April Journal, 2022)
PHBS in schools is an activity to empower students, teachers and the school community to adopt a healthy lifestyle to create healthy schools. This study aims to determine the relationship between knowledge and attitudes with clean and healthy living practices at SD Negeri Rancagoong, Tanjungwangi, Tanjungmedar, Sumedang in 2022. This type of research is cross sectional. The population in the study was all school residents at SD Negeri Rancagoong with a total of 127 people, and the research sample found 56 respondents. The instrument used by distributing questionnaires to respondents. Data were analyzed using chi square. It was found that there was a relationship between knowledge (p = 0.006) and attitudes (p = 0.007) with the practice of PHBS in schools. There is a significant relationship between knowledge and attitudes with PHBS practices in schools. For school residents to be able to apply Clean and Healthy Behavior (PHBS) in the school environment